2010
DOI: 10.1007/s11116-010-9262-4
|View full text |Cite
|
Sign up to set email alerts
|

Getting by with a little help from my friends…and family: immigrants and carpooling

Abstract: While much of the scholarly literature on immigrants' travel focuses on transit use, the newest arrivals to the United States make over twelve times as many trips by carpool as by transit. Using the 2001 National Household Travel Survey and multinomial logit mode choice models, we examine the determinants of carpooling. In particular, we focus on the likelihood of carpooling among immigrants-carpooling both within and across households. After controlling for relevant determinants of carpooling, we find that im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 22 publications
2
66
1
Order By: Relevance
“…Additionally, these enclaves provide selfemployment opportunities for people offering ethnically sensitive products and services [11]. Transportation scholars have found that these enclaves provide major support for social networks that in turn furnish a large share of transportation resources [4]; thus, immigrants living in enclaves have a higher likelihood of carpooling or taking public transit. By relying on these shared transportation resources, especially informal ones, immigrants improve their access to employment, socialization, and other daily activities, thereby enhancing the social capital of their ethnic neighborhood.…”
Section: The Travel Behavior Of Residents Of Immigrant Neighborhoodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, these enclaves provide selfemployment opportunities for people offering ethnically sensitive products and services [11]. Transportation scholars have found that these enclaves provide major support for social networks that in turn furnish a large share of transportation resources [4]; thus, immigrants living in enclaves have a higher likelihood of carpooling or taking public transit. By relying on these shared transportation resources, especially informal ones, immigrants improve their access to employment, socialization, and other daily activities, thereby enhancing the social capital of their ethnic neighborhood.…”
Section: The Travel Behavior Of Residents Of Immigrant Neighborhoodsmentioning
confidence: 99%
“…Many previous studies have found that immigrants in ethnic enclaves, in comparison to native-born residents and immigrants living in other neighborhoods, tended to travel more often by carpooling, public transit and other alternative modes [4]. Immigrants living in neighborhoods with higher ethnic concentration were much more likely to carpool [48,52].…”
Section: The Travel Behavior Of Residents Of Immigrant Neighborhoodsmentioning
confidence: 99%
See 3 more Smart Citations